ANALISIS PENGARUH FAKTOR MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. SALIM TIRTA - H.Samosir, Holder (MAJALAH ILMIAH WIDYA, 2012)
Nowadays, the competition of the various type industrial world is very tight progressively. CV.SALIM Tirta as one of supplier / atransportation company whose business is moving the mineral water from mountain tries to fulfil the customer satisfation and to motivatetheir employees in order to increase the productivity.The aim of this research is to know the company policy in employees motivatingand the find out the corelation between motivation to work productivity. The method used was field Research and secundary datacollected from Library Research.. The result of the research indicated that (1) the work productivity its employees in obtaining equalto r = 0,9 meaning very strong / factor influence motivate to work productivity of employees significant, (2) hypothesis examination inearning t calculate 12,4 > t tables of 1,677 in accepted, there is (relation) and influence between factor motivate with the workproductivity of CV. Salim Tirta of employees.